Metatarsophalangeal joint arthroplasty with implantation of Osteomed Interflex IPG system: our experience - Sperati, G. (Acta Biomedica Atenei Parmensis, 2014)
The Osteomed Interflex IPJ system is a stemmed flexible implant specifically designed for replacement of metatarso-phalangeal joints of the lesser toes. The indication for use is a semi-rigid or rigid hammertoe deformity, impaired function and stability, metatarsal pain. The purpose of the study is the result of 45 implants, in 29 patients (27 women and 2 men). The average of the patients at the time of the operations was 65 years. The follow-up is 30 months. In our experiences this surgical replacement is a good solutions in selectionated cases of metatarso-phalangeal deformity.